HARMONIZATION OF TYPES OF FABRIC ART PROCESSING TO STUDENTS - Muzafarovna, Avlikakulova Nafisa (International Journal of Psychosocial Rehabilitation, 2020)
The summary of the article is: To give an idea about the Uzbek applied art and its peculiarities, to learn to perceive works of applied art. I tried to learn more about the ancient history and technology of gold-embroidery, embroidery, and botanical art. Basically, it provides lessons on the art of fabric making, combining patterns, creating appropriate compositions, choosing the right color relationships, and improving the effectiveness of compositional laws using new innovative technologies